Increased risk of death following release from incarceration: an individual participant data meta-analysis of 1,314,568 adults in eight countries. - Borschmann, Rohan; Keen, Claire; Young, Jesse; Kinner, Stuart (International Journal of Population Data Science, 2022)
Objectives People released from incarceration are at increased risk of death from diverse causes. We aimed to calculate the incidence of all-cause and cause-specific death after release from incarceration and identify individual-level risk factors for death. Approach We conducted a series of individual participant data meta-analyses using data from >1.3 million adults released from incarceration in eight countries from 1980-2018. We used random effects meta-analysis to estimate the pooled all-cause and cause-specific crude mortality rates (CMRs), with 95% confidence intervals (CI) for the entire follow-up period, and for specific time periods after release from incarceration, overall and stratified by age, sex, and region. Results We included 1,395,318 people, 10,164,341 person-years of follow-up time, and 72,920 deaths in our analyses. The overall pooled CMR was 727 (95%CI: 623-840) per 100,000 person-years, with no difference between males and females. The risk of death was highest during the first week following release (all-cause CMR: 1,612, 95%CI: 1048-2,287, I2=91.5%), and the three most common causes of death across the entire follow-up period were 1) alcohol and other drug poisoning (CMR=144, 95%CI: 99-197); 2) cardiovascular disease (CMR: 102, 95%CI: 85-121); and 3) cancer and other neoplasms (CMR=74, 95%CI: 85-121). Leading causes of death varied across time periods following release from incarceration. Conclusion Our findings indicate the need for routine monitoring of mortality following release from incarceration. The distribution of cause of death varies over time, such that clinical decision-making needs to be informed by the proximity to release from incarceration. The elevated risk of death in first 7 days following release highlights the urgent need for coordinated transitional care – including substance use and mental health treatment – and injury prevention initiatives.